MENINGKATKAN PERILAKU ENTREPENEURSHIP KARYAWAN MELALUI KEPERCAYAAN TERHADAP PIMPINAN DAN STRUKTUR ORGANISASI - Sugiharti Sugiharti (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2018)
Employe entrepreneurial behavior are considered to be animportant driver of innovation and strategic renewal withincompanies. This paper focuses on employee behaviour and how it canbe stimulated towards entrepreneurship. We propose and test a two-step model where formal and informal work context affectsemployees’ entrepreneurial behaviour, which then provides the basisfor bottom-up initiated entrepreneurial projects. Our empirical dataconsist of questionnaire responses of 176 employees in Star HotelSemarang. The results of structural equation model estimationsindicate that organisational structure affect employees’entrapreneurial behaviour, but also trust in the direct manager. Wealso find that innovativeness and personal initiative, but not risktaking, play a role for an effective translation of employees’ behaviourinto entrepreneurial projects.